1999
DOI: 10.1128/jb.181.5.1555-1561.1999
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan-Hydrolyzing Activity of the FlgJ Protein, Essential for Flagellar Rod Formation in Salmonella typhimurium

Abstract: Because the rod structure of the flagellar basal body crosses the inner membrane, the periplasmic space, and the outer membrane, its formation must involve hydrolysis of the peptidoglycan layer. So far, more than 10 genes have been shown to be required for rod formation inSalmonella typhimurium. Some of them encode the component proteins of the rod structure, and most of the remaining genes are believed to encode proteins involved in the export process of the component proteins. Although FlgJ has also been kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(93 citation statements)
references
References 37 publications
3
89
0
1
Order By: Relevance
“…Taken together, these results indicate that, although the N-terminus of AcmA contains the active site, the presence of at least one complete repeat is needed for the enzyme to retain appreciable activity in vitro, whereas optimal activity is obtained with three repeats. A similar result was obtained for the active site domain of the FlgJ protein of S. typhimurium, a muramidase-like enzyme involved in flagellar rod formation [10]. The N-terminal half of FlgJ is dispensable for peptidoglycan-hydrolyzing activity in vitro, but the truncated protein does not support cellular flagellation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taken together, these results indicate that, although the N-terminus of AcmA contains the active site, the presence of at least one complete repeat is needed for the enzyme to retain appreciable activity in vitro, whereas optimal activity is obtained with three repeats. A similar result was obtained for the active site domain of the FlgJ protein of S. typhimurium, a muramidase-like enzyme involved in flagellar rod formation [10]. The N-terminal half of FlgJ is dispensable for peptidoglycan-hydrolyzing activity in vitro, but the truncated protein does not support cellular flagellation.…”
Section: Discussionsupporting
confidence: 76%
“…However, the AcmA homologs AcmB [7], AcmC [8] and LytG [9] have been shown to be glucosaminidases. Amino acid substitutions in the AcmA homolog FlgJ of Salmonella typhimurium have shown that two conserved amino acid residues, aspartyl and glutamyl, which are also preserved in AcmA, muramidase-2 and LytG, are part of the putative active center of this peptidoglycan hydrolase that is essential for flagellar rod formation [10]. In the sequence of the genome of L. lactis IL1403 genes putatively encoding cell wall hydrolases with an active site homologous to that of AcmA are present (acmB, acmC and acmD).…”
mentioning
confidence: 99%
“…Comparison of the predicted amino acid sequence of Mur1 with protein sequence databases revealed sequence identity, in its 72^218 amino acid region, with E. hirae muramidase-2 (55%) [8], E. faecalis autolysin (54%) [2] and L. lactis AcmA (52%) [5]. Sequence identity was also found with the ORF39 of the B. subtilis phage P105 (sequence accession number AB016282) (42.7%) and the B. subtilis hypothetical muramidase YubE (41%) (sequence accession number O32083), which functions are unknown, and with the Salmonella typhimurium £agellar speci¢c muramidase FlgJ (30.3%) [14] (Fig. 1A).…”
Section: Cloning and Nucleotide Sequence Of S Thermophilus Mur1 Genementioning
confidence: 97%
“…1B). Mur1 encompasses exactly the sequence corresponding to the catalytic domain of the enzymes of the muramidase family [5,11,14]. Especially, the Asp and Glu residues, which are conserved in the putative active centre of these enzymes [11], are also present in the corresponding positions of Mur1 (Glu-135 and Asp-161) ( Fig.…”
Section: Cloning and Nucleotide Sequence Of S Thermophilus Mur1 Genementioning
confidence: 99%
“…review the peptidoglycan layer negotiated? Perhaps cellular enzymes that degrade the peptidoglycan might have a function in TolC assembly, analagous to the dedicated muraminidase needed for assembly of flagella on the cell surface (Nambu et al, 1999). Another question relates to how the channel-tunnels are located by substrate-laden IM complexes.…”
Section: Perspectivesmentioning
confidence: 99%